âFLATUSâ: FORMULA ANTI GALAU UNTUKMU SAHABAT - Choirunnisa, Amalia; Laily, Akhiril Fatiya Isnaenil; Baroroh, Avie Avievah; Anisa, Farahdiba; Hadwiono, Muhammad Reyhan (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
Many young people in Indonesia are infected with virus "troubled". If this problem is not resolved, there will be a decrease in quality of life. Teenagers need a positive medium to devote all its problems such as a diary, so they can write whatever perceived and experienced. Diary "flatus" intended to reduce the frustrations of the youth by guiding them to find alternative solutions for the problem, increasing the interest of writing, and help improve the living spirit with motivational words. Until now we have sold 57 pieces of flatus, it proves that the product is in high demand.